A possible mechanism for the suppression of Plasmodium berghei development in the mosquito Anopheles gambiae by the microsporidian Vavraia culicis. - Irka Bargielowski (Public Library of Science (PLoS), 2009)
Background Microsporidian parasites of mosquitoes offer a possible way of controlling malaria, as they impede the development of Plasmodium parasites within the mosquito. The mechanism involved in this interference process is unknown. Methodology We evaluated the possibility that larval infection by a microsporidian primes the immune system of adult mosquitoes in a way that enables a more effective anti-Plasmodium response. To do so, we infected 2-day old larvae of the mosquito Anopheles gambiae with one of 4 isolates of the microsporidian Vavraia culicis and reared one group as an uninfected control. Within each treatment, we fed half the adult females on a mix of P. berghei ookinetes and blood and inoculated the other half with a negatively charged CM-25 Sephadex bead to evaluate the mosquitoes' melanisation response. Conclusions The microsporidian-infected mosquitoes were less likely to harbour oocysts (58.5% vs. 81.8%), harboured fewer oocysts (8.9 oocysts vs. 20.7 oocysts) if the malaria parasite did develop and melanised the Sephadex bead to a greater degree (73% vs. 35%) than the controls. While the isolates differed in the number of oocysts and in the melanisation response, the stimulation of the immune response was not correlated with either measure of malaria development. Nevertheless, the consistent difference between microsporidian-infected and -uninfected mosquitoes--more effective melanisation and less successful infection by malaria--suggests that microsporidians impede the development of malaria by priming the mosquito's immune system.